Modification of diazoquinone-novolac photoresist films by boron ion implantation - Brinkevich, Dmitrii I.; Prasalovich, Uladislau S.; Yankouski, Yury N. (Journal of the Belarusian State University. Physics, 2020)
Diazoquinone-novolac photoresist films implanted with B+ ions were studied by the method of attenuated total reflection (ATR). Films of positive photoresist FP9120 with a thickness h of 1.0 and 2.5 mm were deposited by centrifuging on p-type silicon plates with (111) orientation. Implantation with 60 keV B+ions in the dose range of 1015–1016 cm–2 in the constant ion current mode (current density 4 mA/cm2 ) was carried out at room temperature in a residual vacuum not worse than 10–5 Pa using the «Vesuvius-6» ion beam accelerator. The attenuated total reflection spectra were recorded in the range 400 – 4000 cm–1 by ALPHA spectrophotometer (Bruker Optik GmbH, Germany) at room temperature. It was shown that ion implantation leads to intensive transformation of the photoresist beyond the range of ions, which is characterized by the appearance in the spectrum of intense bands with peaks at 2151 and 2115 cm–1, due to stretching vibrations of double cumulative bonds, in particular С——С——О. In the implanted samples, a shift to the low-energy region of the maxima of the stretching vibrations of C—H bonds, plane deformation vibrations of O—H bonds and pulsating vibrations of the carbon skeleton of aromatic rings as well as the redistribution of intensities between closely spaced maxima, were observed.